Editorial comment - Villa, Luisa Lina (Brazilian Journal of Sexually Transmitted Diseases, 2010)
The path is long and tortuous, obstacles thrive, but solutions to control cervical cancer are available for all to see (or for those who want to see). Three decades of intense scientific research have passed, which generated many studies, debates and thousands of publications, until we learned that cervical cancer is caused by viruses with great potential to cause cancer. Its features were stripped; sneaky invasions identified; the clinical manifestations known in detail, catalogued, and so blatantly labelled as sexually transmitted diseases, with the accompanying prejudice and guilt. But no one is to blame: a ruthless society first judges, then cry for thousands of women killed each year. In addition, we are observing an increase in incidence of precancer and cancer in younger women, a direct result of early exposure to oncogenic HPVs, which they get as soon as they start sexual activity. [...]